2018
DOI: 10.17559/tv-20170124120729
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Molybdenum and Manganese on the Mechanical Properties of Austempered Ductile Iron

Abstract: Abstract:In this review paper an insight is given on how alloying elements and heat treatment parameters affect mechanical properties of austempered ductile irons (ADI).To elevate hardenability or austemperability of large sections, alloying is required during production of ADI. Conventional ductile iron should be enriched with certain alloying elements to obtain ADIs with desired strength and ductility. These elements must ensure that pearlite formation is avoided as well as that austenite is stabilized durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…They decrease the quantity of carbon soluble in the austenite and thus increase the quantity of free carbide in the iron at a given carbon content. Recent research works [13,15,[19][20][21][22][23][24] have shown that, Si, Mn, Ni, Mo, V, Cu, Ti, Nb, W, Sn… are the typical alloying elements used to control ferrite and pearlite contents and increases mechanical properties in ductile iron as-cast grades. Mn and Cu are used to promote pearlite, Si is used to promote ferrite and to strengthen it.…”
Section: Introductionmentioning
confidence: 99%
“…They decrease the quantity of carbon soluble in the austenite and thus increase the quantity of free carbide in the iron at a given carbon content. Recent research works [13,15,[19][20][21][22][23][24] have shown that, Si, Mn, Ni, Mo, V, Cu, Ti, Nb, W, Sn… are the typical alloying elements used to control ferrite and pearlite contents and increases mechanical properties in ductile iron as-cast grades. Mn and Cu are used to promote pearlite, Si is used to promote ferrite and to strengthen it.…”
Section: Introductionmentioning
confidence: 99%